2019
DOI: 10.1137/18m1194729
|View full text |Cite
|
Sign up to set email alerts
|

Obligations with Physical Delivery in a Multilayered Financial Network

Abstract: This paper provides a general framework for modeling financial contagion in a system with obligations in multiple illiquid assets (e.g., currencies). In so doing, we develop a multi-layered financial network that extends the single network of Eisenberg and Noe [2001]. In particular, we develop a financial contagion model with fire sales that allows institutions to both buy and sell assets to cover their liabilities in the different assets and act as utility maximizers.We prove that, under standard assumptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…14,Π i (τ k ) ≥ 0 for all banks i. Let Λ be as in the proof of Lemma 3.14, definethe domain U k = m l=1 Π ∈ [0, 1] n |Λ k l (s ⊤ Π) ≥ 1 2 Λ l (τ k ) whereΛ k : [0, M ] → R m is defined by = ½ {t<τ n−1 }Γ t (t ∧τ k+1 ) f t (t ∧τ k ) 1−αθ min αθ minΛk + ½ {t≥τ n−1 } s i n j=n−1…”
mentioning
confidence: 99%
“…14,Π i (τ k ) ≥ 0 for all banks i. Let Λ be as in the proof of Lemma 3.14, definethe domain U k = m l=1 Π ∈ [0, 1] n |Λ k l (s ⊤ Π) ≥ 1 2 Λ l (τ k ) whereΛ k : [0, M ] → R m is defined by = ½ {t<τ n−1 }Γ t (t ∧τ k+1 ) f t (t ∧τ k ) 1−αθ min αθ minΛk + ½ {t≥τ n−1 } s i n j=n−1…”
mentioning
confidence: 99%
“…After applying the method to the European bank's dataset, they found that the perturbation of relative liabilities may lead to huge economic differences, which may underestimate the risk of infection. Banerjee andFeinstein (2019), Feinstein (2019), Veraart (2020), and Barucca et al (2020) explored financial systemic risk from the aspect of interdependent liabilities, a multilayered financial network, stress testing, and credit risk, respectively.…”
Section: Local Forward Main Path Of Financial Systemic Risk Researchmentioning
confidence: 99%
“…Related work is the approach by Feinstein (2017) who considers an extension of the single network approach by Eisenberg & Noe (2001) to a multi-layered financial network to study contagion in multiple asset classes. This approach could also be applied to a multi-period or multi-maturity setting.…”
Section: Literature Reviewmentioning
confidence: 99%